Potential antihyperlipidemic polyketones from endophytic Diaporthe sp. JC-J7 in Dendrobium nobile1. Issue 73 (14th December 2018) - Hu, Ming; Yang, Xue-Qiong; Wan, Chuen-Ping; Wang, Bang-Yan; Yin, Hai-Yue; Shi, Li-Jiao; Wu, Ya-Mei; Yang, Ya-Bin; Zhou, Hao; Ding, Zhong-Tao
Abstract : Eleven new polyketones were isolated from Diaporthe sp. JC-J7, and some compounds indicated antihyperlipidemic activity. Abstract : Eleven new polyketones named diaporthsins A–K (1–11 ) were isolated from the fermentation of Diaporthe sp. JC-J7. The chemical structures of compounds (1–11 ) were elucidated by spectroscopic methods including HRESIMS, 2DNMR, NMR and chemical methods. Compound11 features an unusual acyclic polyketone–phenolic polyketone hybrid structure that integrates the characteristics of different fungal metabolites (cytosporone and multiplolide). Compound3 was the only C12 -polyketone obtained in this research. These new polyketones showed inhibitory activity on triglycerides (TG) in steatosis hepatocyte L-02 cells. Among them, compound5 and (4 E )-6, 7, 9-trihydroxydec-4-enoic acid displayed inhibitory activities on TG in steatotic L-02 cells with inhibition ratios of 26% and 21% at concentration of 5 μg mL −1 ; also, inhibition ratios of 8- O -acetylmultiplolide A and phomopsisporone A at concentration of 5 μg mL −1 were calculated to be about 24% and 16%, respectively, which were equivalent to the antihyperlipidemic activity of lovastatin. The preliminary structure–activity relationship indicated that acetyl at C-8 can increase the antihyperlipidemic activity of multiplolide A and the glycol ester and hydroxyl at C-6 can also increase the corresponding activity of diaporthsin B.